Determinants of customers' choice of dining-related services: the case of Taipei City. Issue 5 (30th March 2020) - Cheng, Ching-Chan; Wu, Hung-Che; Tsai, Ming-Chun; Chang, Yu-Yuan; Chen, Cheng-Ta
Abstract : Purpose: This study aims to extract determinants of customers' choice of dining-related services (CDS) to understand their attitudes and habits for dining-related services. Moreover, it classifies restaurant customers into several clusters based on their CDS factors and further analyzes the differences in the preferences and habits for dining-related services among various clusters. Design/methodology/approach: This study extracts the CDS factors using principal component analysis and identifies construct validity of the CDS factors through the results of confirmatory factor analysis. Then, it divides the restaurant customers in Taipei City into different clusters through cluster analysis to explore the habits and preferences for dining-related services in each cluster. Findings: The study results show that the extracted six CDS factors, including service commitment, dietary preferences, design styles, additional value, delicate information collection, and dining environments. Dietary preferences, service commitment and additional value factor are the most important CDS factors for restaurant customers in Taipei City. This study divides 1, 029 restaurant customers in Taipei City into three clusters based on the CDS factors through cluster analysis. The differences in the preferences and habits for dining services among three clusters have been discussed in the context in detail. Finally, this study develops eight service strategies and determines the order of execution of the eight service strategies for each cluster of customers. Originality/value: The findings will help restaurant operators segment the market, target market customers, carry out service positioning and develop marketing strategies to respond to the highly competitive restaurant market and achieve sustainable restaurant operations.